2022
DOI: 10.3390/cancers14236014
|View full text |Cite
|
Sign up to set email alerts
|

Dual LSD1 and HDAC6 Inhibition Induces Doxorubicin Sensitivity in Acute Myeloid Leukemia Cells

Abstract: Defects in epigenetic pathways are key drivers of oncogenic cell proliferation. We developed a LSD1/HDAC6 multitargeting inhibitor (iDual), a hydroxamic acid analogue of the clinical candidate LSD1 inhibitor GSK2879552. iDual inhibits both targets with IC50 values of 540, 110, and 290 nM, respectively, against LSD1, HDAC6, and HDAC8. We compared its activity to structurally similar control probes that act by HDAC or LSD1 inhibition alone, as well as an inactive null compound. iDual inhibited the growth of leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Moreover, histone deacetylases (HDACs) are highly expressed in various cancers, 50 and recent research has reported that lysine-specific demethylase 1 (LSD1)/ HDAC6 multitargeting inhibitors can induce DOX sensitivity in acute myeloid leukemia cells. 51 Together, these results expand our understanding of the ac 4 C epitranscriptome and hold great potential to overcome the drug resistance of CML.…”
Section: ■ Conclusionmentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, histone deacetylases (HDACs) are highly expressed in various cancers, 50 and recent research has reported that lysine-specific demethylase 1 (LSD1)/ HDAC6 multitargeting inhibitors can induce DOX sensitivity in acute myeloid leukemia cells. 51 Together, these results expand our understanding of the ac 4 C epitranscriptome and hold great potential to overcome the drug resistance of CML.…”
Section: ■ Conclusionmentioning
confidence: 67%
“…Intriguingly, acetylation enhances mRNA stability and translation efficiency and its presence within the wobble position of tRNA promotes translation, 4 which is reminiscent of the activating effect of histone acetylation. Moreover, histone deacetylases (HDACs) are highly expressed in various cancers, and recent research has reported that lysine-specific demethylase 1 (LSD1)/HDAC6 multitargeting inhibitors can induce DOX sensitivity in acute myeloid leukemia cells . Together, these results expand our understanding of the ac 4 C epitranscriptome and hold great potential to overcome the drug resistance of CML.…”
Section: Discussionmentioning
confidence: 90%
“…However, apoptosis presents itself as a double-edged sword. In fact, it can be the problem and also provide a potential solution, since drugs aimed at activating and/or increasing apoptotic pathways are indeed coveted therapeutic options, especially in the field of leukemia ( Peng et al, 2016 ; Bulut et al, 2022 ). In this scenario, Ca 2+ influx is the master second messenger that influences the proliferation–apoptosis balance: low intracellular levels are required for cell growth stimulation, while its overload is strongly responsible for apoptosis induction ( Shapovalov et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…at designed a potent and selective dual LSD1/ HDAC6 inhibitor iDual (Table 3, Figure 6), a hydroxamic acid analogue of GSK2879552. 143 iDual effectively inhibited LSD1, HDAC6, and HDAC8 with IC 50 values of 540, 110, and 290 nM, respectively. Furthermore, iDual demonstrated a higher level of growth inhibition in leukemia cell lines THP-1 and MOLM-13 with micromolar IC 50 values than GSK2879552.…”
Section: Co-inhibitors Of Lsd1 Andmentioning
confidence: 97%
“…Bulut et. at designed a potent and selective dual LSD1/HDAC6 inhibitor iDual (Table , Figure ), a hydroxamic acid analogue of GSK2879552 . iDual effectively inhibited LSD1, HDAC6, and HDAC8 with IC 50 values of 540, 110, and 290 nM, respectively.…”
Section: Co-inhibitors Of Lsd1 and Other Targetsmentioning
confidence: 99%